POJĘCIE BAZY DANYCH NA GRUNCIE USTAWY O PRAWIE AUTORSKIM I PRAWACH POKREWNYCH ORAZ USTAWY O OCHRONIE BAZ DANYCH - Górecka, Anna (Zeszyty Prawnicze, 2017)
CONCEPT OF A DATABASE IN BASIS OF COPYRIGHT AND NEIGHBOURING RIGHTS ACT AND DATABASE PROTECTION Summary Collecting and processing of different kinds of data is commonly practiced nowadays. The novelty under the polish law is an introduction of the legal protection of such data bases. This protection is provided in two particular regulations: the act on copyrights and neighbouring rights of 4th February 1994 and the act on the protection of the database of 27thJuly 2001. The database is defined as any kind of collections, lists of information, materials or any other elements systemized according to specified criterion. Its essence consists in collecting and confronting given data using the settled method but not in the materials collected in such kind of evidence. Any database consists of various information thus it is treated as a collection of materials. That is of no importance if the collected elements are subject to the legal protection therefore it seems that such collection may contain any data not only these protected under the copyrights and it does not matter if they are protected under the law or no or if they are confidential or easy available. Each of the regulations mentioned above provides the different system of protection. The act on copyrights regards the external aspects of a collection (the creativity must consist in a selection, systématisation or confrontation of the information) and protects only the creative elements of the collection. Thus with regard to databases (constituting protected good within the meaning of the copyrights law) it must be noticed that they will be protected only within the scope of their creativity that could be however expressed in many aspects. The other regulation gives the possibility of protecting the contents of the database (the internal aspect of the database). Applicability of one of these regulations excludes applicability of the other as the article 1 of the law on the protection of the database states that the object of the legal protection under this law is a database which does not constitute protected good within the meaning of the law on copyrights. However such database has to comply with the requirement of a substantial investment. Such substantial investment has to be undertaken in order to prepare, verify or present the contents and it may consist in the quality as well as the quantity of the investment while the method of the collection of the data is unrestricted. Thus there is no possibility of the cumulative protection of the database. However it was constituted the new and genuine right allowing collection of the data and its subsequent processing as a whole or in part, according to both the quality as well as the quantity. Such right is of the exclusive and transferable nature.